Human pluripotent stem cell-derived cardiomyocytes as research and therapeutic tools - Acimovic, Ivana; Vilotic, Aleksandra; Pesl, Martin; Lacampagne, Alain; Dvorak, Petr; Rotrekl, Vladimir; Meli, Albano C (BioMed research international, 2014)
Human pluripotent stem cells (hPSCs), namely, embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), with their ability of indefinite self-renewal and capability to differentiate into cell types derivatives of all three germ layers, represent a powerful research tool in developmental biology, for drug screening, disease modelling, and potentially cell replacement therapy. Efficient differentiation protocols that would result in the cell type of our interest are needed for maximal exploitation of these cells. In the present work, we aim at focusing on the protocols for differentiation of hPSCs into functional cardiomyocytes in vitro as well as achievements in the heart disease modelling and drug testing on the patient-specific iPSC-derived cardiomyocytes (iPSC-CMs).
Keywords: výzkum kmenových buněk; kardiomyocyty; Humans; Pluripotent Stem Cells; Myocytes, Cardiac; pluripotentní kmenové buňky; Stem Cell Research; lidé